2019
DOI: 10.2478/manment-2019-0026
|View full text |Cite
|
Sign up to set email alerts
|

Academic Staff Direct Participation in Managing Higher Education Institutions – Pilot Study Report

Abstract: The aim of the study is to present the results of pilot study on academic staff direct participation (ASDP) in managing higher education institutions (HEI) (content, scope, intensity, practicality of impact), in key areas of its activity and its advantages and risks. The research was carried out under questionnaire survey method among academic staff of selected HEIs, in autumn 2018. It was found that ASDP applies to all areas of activity of these HEIs (content), primarily educating students; is full (academics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Mainly, they found that HEIs have a quality of education due to the HC that is difficult to simulate or copy (Szelagowskarudzka, 2019). They also ascertained the HC as non-sustainable.…”
Section: Human Capitalmentioning
confidence: 99%
“…Mainly, they found that HEIs have a quality of education due to the HC that is difficult to simulate or copy (Szelagowskarudzka, 2019). They also ascertained the HC as non-sustainable.…”
Section: Human Capitalmentioning
confidence: 99%